2016
DOI: 10.1007/s13280-016-0789-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the export and concentrations of organic carbon, nitrogen and phosphorus in boreal lakes by catchment characteristics and land use: A practical approach

Abstract: The majority of C, N and P in boreal lakes are in organic form. Organically bound nutrients are released through biodegradation or photodegradation which affects the water quality, eutrophication and greenhouse gas emissions of lakes. We tested whether open land-use data combined with land-use-specific export coefficients can be used to predict total organic carbon (TOC), dissolved organic nitrogen (DON) and dissolved organic phosphorus (DOP) loading and lake water concentrations. Using data from 12 lake catch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 63 publications
(103 reference statements)
0
30
0
Order By: Relevance
“…The dominance of cyanobacteria in browning temperate lakes may be related to longer and warmer growing season and higher nutrient levels or less acidic conditions compared to the naturally brown boreal lakes in the current study (Palviainen et al 2016, Senar et al 2019. This is supported by the results from Lake € At€ ask€ o in the current study, which was the only lake with any relevant anthropogenic input of carbon and nutrients (Palviainen et al 2016). Lake € At€ ask€ o was distinct from the other high DOC lakes due to its absence of Gonyostomum and correspondingly lower phytoplankton biomass and PUFA concentration (although not as low as in the oligotrophic lakes), which is in accordance with previous studies (Bergstr€ om and Karlsson 2019, Senar et al 2019.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The dominance of cyanobacteria in browning temperate lakes may be related to longer and warmer growing season and higher nutrient levels or less acidic conditions compared to the naturally brown boreal lakes in the current study (Palviainen et al 2016, Senar et al 2019. This is supported by the results from Lake € At€ ask€ o in the current study, which was the only lake with any relevant anthropogenic input of carbon and nutrients (Palviainen et al 2016). Lake € At€ ask€ o was distinct from the other high DOC lakes due to its absence of Gonyostomum and correspondingly lower phytoplankton biomass and PUFA concentration (although not as low as in the oligotrophic lakes), which is in accordance with previous studies (Bergstr€ om and Karlsson 2019, Senar et al 2019.…”
Section: Discussionmentioning
confidence: 63%
“…Cyanobacteria do not contain any EPA or DHA but may contain C18 PUFA (Los and Mironov 2015), thus maintaining some level of PUFA production (Strandberg et al 2015b). The dominance of cyanobacteria in browning temperate lakes may be related to longer and warmer growing season and higher nutrient levels or less acidic conditions compared to the naturally brown boreal lakes in the current study (Palviainen et al 2016, Senar et al 2019. This is supported by the results from Lake € At€ ask€ o in the current study, which was the only lake with any relevant anthropogenic input of carbon and nutrients (Palviainen et al 2016).…”
Section: Discussionmentioning
confidence: 67%
“…The low DOC : DON and DOC : DOP ratios observed in catchments where agricultural and heavily fertilized land classifications dominate (IG and AH) is a pattern consistent within the wider literature (Aitkenhead‐Peterson et al ; Graeber et al ; Heinz et al ; Williams et al ). Removal of crop residues and well‐maintained field drainage systems in areas with intensive arable production have been found to reduce soil organic matter content while also reducing contact time between water and soil organic material, thus reducing organic matter dissolution rates (Mattsson et al ; Palviainen et al ). In addition, physical disturbances from agricultural practices and higher soil pH have been shown to increase soil DOM turnover rates (Leifeld et al ).…”
Section: Discussionmentioning
confidence: 99%
“…However, catchments impacted by agricultural intensification (Graeber et al ; Yates et al ), subject to urbanization (Aitkenhead‐Peterson et al ), or heavily impacted by sewage treatment works (STWs; Sickman et al ; Yates et al ), have demonstrated increases in both DOM concentration and its relative nutrient richness (measured as DON and DOP). Not only is DOM concentration therefore known to vary in relation to catchment character (Palviainen et al ) but also a wide range of studies have observed compositional differences in DOM related to specific catchment sources (Mattsson et al ; Spencer et al ; Hernes et al ; Yates et al ). These differences reflect the influence of land use and management, soil type, and hydrological function in controlling the rates of microbial decomposition, nutrient cycling, uptake within the soil, and the net flux of DOM from different soil horizons to adjacent waters (Austnes et al ).…”
mentioning
confidence: 99%
“…Combining the results with existing literature including data regarding the average properties of head water catchments in Central Finland (Korkalainen et al 2007), and a biodegradation equation with parameters (Kalbitz et al 2003a), transport time, role of biodegradation in the transport and the DOC export load to watercourse can be produced. By means of more complex initial information, such as water flow path characteristics of the catchment, hydraulic characteristics, soil types, and experimental parameters, more precise computational remarks can be obtained (Palviainen et al 2016). The calculation in II indicates that enchytraeids can increase the DOC export load from 14 to 20 ha -1 yr -1 .…”
Section: Implications For the Export Of C And Nmentioning
confidence: 99%